UPAYA MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MELALUI BIMBINGAN BERKELANJUTAN - R Suhartini (Universitas Nasional, 2020)
Education is an investment in human resource development and is seen as a basic need for people who want to progress. The components of the education system that includes human resources can be classified into two namely: teacher and non-teacher education personnel. According to Law No. 2 of 2003 concerning the National Education System states,